2013
DOI: 10.1111/pai.12048
|View full text |Cite
|
Sign up to set email alerts
|

A randomized maternal evaluation of epinephrine autoinjection devices

Abstract: It is concerning that 15% of mothers overall could not 'fire' these devices correctly despite a one-to-one demonstration, identifying a need for more user friendly devices and training. Mothers found the Anapen(®) device significantly easier to use, which may have implications for future prescribing. Evaluation of the next generation of autoinjectors and their training packages needs to be performed as important practical differences may be found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 20 publications
2
62
2
Order By: Relevance
“…There is no blinded research assessing real-world epinephrine autoinjector technique in pharmacists, patients or other health professionals. Although Anapen is available in the United Kingdom, Europe and Australia, there is no research evaluating its demonstration by pharmacists, and few evaluations in other groups [23, 27]. …”
Section: Introductionmentioning
confidence: 99%
“…There is no blinded research assessing real-world epinephrine autoinjector technique in pharmacists, patients or other health professionals. Although Anapen is available in the United Kingdom, Europe and Australia, there is no research evaluating its demonstration by pharmacists, and few evaluations in other groups [23, 27]. …”
Section: Introductionmentioning
confidence: 99%
“…First, the majority of participants in these studies were self-selected with often no description of differences between responders and non-responders, and may reflect responder bias. However, we know from a recent study involving mothers of non-allergic children with no previous experience of AAIs that only 15% were able to administer the device,32 a figure which falls in the range of correct administration scores by experienced parents/caregivers found in this systematic review (6%–57%). Second, although the majority of studies used demonstration to assess administration (82%), self-reported questionnaires were used in the remaining studies indicating that findings may not reflect actual behaviour.…”
Section: Discussionmentioning
confidence: 68%
“…However, even after intensive education, errors and mistakes still occur. In one study, 15% of the mothers with no previous EAI experience were unable to activate the device successfully despite a personalized demonstration with an EAI trainer immediately before testing, leading the investigators to conclude that this identified a need for more user-friendly devices and training [32].…”
Section: Training and Retention Of Skillsmentioning
confidence: 94%
“…The physical features (particularly the size) of the device influenced the decision of the others not to carry it consistently Money et al (2013) [27] The design of EAIs should receive attention as patients often fail to carry them owing to size and esthetics Simons et al (2010) [28] Unintentional injections from EAIs increased annually from 1994 to 2007, suggesting that improved EAI design is needed, along with increased vigilance in training the trainers and the users Arga et al (2011) [29] Ongoing mistakes in EAI use that occur despite integrated theoretical and practical education might be related to its design [30] Competence in using EAIs was associated with regular visits to the allergy clinic and decreased as time elapsed from first EAI instruction to the last visit, indicating that acquired skills are not permanent [31] Medical interns' competence with EAIs was maintained for the first 3 months after training but decreased by 6 months, suggesting that frequent regular retraining is needed Brown et al (2013) [32] Immediately after a one-to-one demonstration, 15% of mothers who had no experience with EAIs could not 'fire' an EAI device correctly, identifying a need for more user-friendly devices and training Chad et al (2013) [33] 56% (672 of 1209) of parents expressed fear about EAI use: specifically, fear of hurting the child, using the EAI incorrectly, or a bad outcome Schwirtz and Seeger (2010) [34] Data on mechanical stress and injection performance characteristics indicated significant limitations in the design and quality of the EAIs tested Auvi-Q-specific references…”
Section: Eai References Key Messagementioning
confidence: 96%